KARAKTERISTIK RUANG PADA RANCANGAN ARSITEKTUR DENGAN KONSEP SUPERIMPOSISI DAN HIBRID DALAM TEORI FUNCTION FOLLOW FORM - Pujantara, Ruly (Universitas Negeri Makassar, 2014)
In Function Follow Form Theory, form is a major focus in the design, making visual acceleration is very important, while the function of the space must be able to follow and set based on pre-existing forms. This theory also spawned the development of concepts forming and shaping a more advanced, such as the superimposition and hybrid. Furthermore, advancing of how to combine and blend adaptively the geometric forms as a free and non free direction. With these forms, the layout planning, configuration and interaction of existing space in the shell form of brutality becoming a special concern in the design, because of the design process will be reversed in the review of its design criteria for a functional space requirements such as air conditioning, lighting, acoustics and flow circulation. Keywords: Space and Place, Superimposition Hybrid Architecture, Architecture Brutalism